A Study on the Effects of Different Heat‐Treatment Parameters on Microstructure–Mechanical Properties and Corrosion Behavior of Maraging Steel Produced by Direct Metal Laser Sintering. Issue 10 (28th July 2020) - Özer, Gökhan; Karaaslan, Ahmet
Abstract : Herein, direct aging (aged‐490 °C/6 h) and solution heat treatment and subsequent aging (SHT‐940 °C/2 h + 490 °C/6 h) heat treatments are applied to maraging steel (MS1) produced by direct metal laser sintering (DMLS) method. The effects of these heat treatments on microstructure, phase transformations, mechanical properties, and corrosion properties in MS1 are given in comparison with the as‐built state. Optical microscope (OM) and scanning electron microscope (SEM) is used for microstructure measurements, electron dispersion spectroscopy (EDX), differential scanning calorimetry (DSC), and X‐ray diffraction (XRD) methods are used to determine the phase transformations. Potentiodynamic polarization tests are applied to determine the corrosion resistance of the material, and stereo OM and the Tafel extrapolation method is used to examine the corrosion results. The hardness test is carried out with a Rockwell C method to determine the mechanical character of the material. According to the results obtained, it is determined that the applied heat treatments affect the hardness and corrosion resistance of the material by changing the microstructure and phase transformations of MS1 material produced with DMLS. Abstract : The maraging steel (MS1) produced by the direct metal laser sintering (DMLS) method has a unique microstructure. This microstructure varies considerably with the applied heat‐treatment parameters. In this case, it significantly affects the precipitate distribution and corrosion properties of the material.